2012
DOI: 10.1007/s00520-012-1620-7
|View full text |Cite
|
Sign up to set email alerts
|

Low body mass index as a risk factor of moderate to severe oral mucositis in oral cancer patients with radiotherapy

Abstract: Low BMI may be a risk factor of moderate to severe oral mucositis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 14 publications
1
17
1
1
Order By: Relevance
“…Previous studies have suggested hemoglobin levels and body mass index are correlated with the severity of radiotherapy induced OM severity. [ 17 , 33 ] In contrast, this current study did not detect association of these factors with oral mucosal reaction. These results may be due to the fact that most study subjects had relatively normal hemoglobins and BMIs.…”
Section: Discussioncontrasting
confidence: 97%
See 1 more Smart Citation
“…Previous studies have suggested hemoglobin levels and body mass index are correlated with the severity of radiotherapy induced OM severity. [ 17 , 33 ] In contrast, this current study did not detect association of these factors with oral mucosal reaction. These results may be due to the fact that most study subjects had relatively normal hemoglobins and BMIs.…”
Section: Discussioncontrasting
confidence: 97%
“…Currently many factors have been associated with OM. The most commonly recognized risk factors for OM include poor oral hygiene and periodontal disease, [ 14 ] chronic alcohol consumption, cigarette smoking, [ 15 ] hyposalivation, [ 16 ] low body mass index (BMI < 18.5), [ 17 ] as well as concurrent diseases such as diabetes mellitus. In addition, age, sex and therapeutic regimen have been suggested as risk factors.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous study also found that body weight loss ≥ 5% was a related risk factor to severe ROM ( 19 ). Two other studies conducted in oral cavity cancer patients found that lower BMI was significantly related with severe ROM ( 49 , 50 ). The underlying mechanism might be that malnutrition could interfere with mucosal regeneration due to decreased cellular migration and renewal resulting from poor nutrition status ( 51 ).…”
Section: Discussionmentioning
confidence: 88%
“…Some studies have reported an association between poor nutrition and development of mucositis [35][36][37]. The potential mechanism of the association between BMI and oral mucositis is uncertain [38]. Oral mucositis is one of the most serious problems connected to head and neck cancer radiotherapy [39,40], and severe cases may require feeding tube placement.…”
Section: Discussionmentioning
confidence: 99%
“…After this time period, oral mucositis did not differ significantly between the groups. Saito et al [38] examined whether low BMI could be a risk factor for oral mucositis. In their study, 33 patients with oral cancer received radiotherapy and they found that low BMI (< 22) may be a risk factor of moderate to severe oral mucositis.…”
Section: Discussionmentioning
confidence: 99%